Inequality in Earnings and Adverse Shocks in Early Adulthood - Adoho, Franck M.; Tien, Bienvenue N. (World Bank, Washington, DC, 2018)
The inequality of opportunity theory postulates that achievement gaps arising because of factors beyond the individual's control are morally unacceptable and should therefore be compensated by society. These factors or circumstances range from the individual's social background to adverse shocks. Most studies have focused on the contribution of social background and genetic and other childhood-related circumstances to inequality of opportunity. Borrowing insights based on the impressionable years hypothesis in social psychology, this paper tests how exposure to adverse shocks, such as war, in early adulthood (ages 18-25) affects the individual's future labor earnings and subsequently contributes to earnings inequality. The application to the Democratic Republic of Congo is associated with two significant takeaways. First, all else equal, individuals who experience intensely violent conflict at a young age earn significantly less than their counterparts. Second, after controlling for the individual's social background, the share of overall inequality in earnings accounted for by the experience of adverse shocks in early adulthood is not negligible, ranging from 2.5 to 3.5 percent. These insights broaden our understanding in the discussion on inequality of opportunity and represent a new path in the design of allocation policies that seek to reduce inequality and poverty.